Influence of exogenous gibberellin (GA3) on fruit quality in different peach varieties (strains) - CHEN Hong; DU Jinhua; MA Ruijuan; ZHANG Yuanyuan; DING Hui; ZHANG Binbin; YU Mingliang (Guoshu xuebao)
[Objective] Exogenous GA3 is widely used to regulate fruit growth and development, which is closely related to fruit quality. The sensitivity of exogenous GA3 varies among different fruit tree species. The aim of this study was to investigate the effects of exogenous GA3 at different concentrations on single fruit mass, fruit shape index, colour values, firmness, soluble solids content (SSC), soluble sugar content, organic acid content, and sugar-acid ratio of different peach varieties (strains). [Methods] Peaches of DB2-9, Xiahui 8 and Xiacui were used as experimental materials. The experiment included 4 treatments: T1 (spraying water), T2 (50 mg·L-1 GA3), T3 (100 mg·L-1 GA3), and T4 (150 mg·L-1 GA3), and each treatment included three trees that were sprayed four times at intervals of 10 d, starting from 48, 50, and 46 d after full bloom, respectively. Twenty fruits were randomly collected from each treatment (three replications) at the hard core stage, expansion stage and ripening stage for the determination of external and internal fruit mass indexes. All data were statistically analyzed. [Results] In this study, the mass of single fruit of Xiahui 8 and Xiacui in T2 treatment was significantly higher than in the other treatments during the expansion and ripening stages; during the ripening period, the mass of single fruit of DB2-9 under T2 and T3 was significantly higher than under T1 and T4. During the expansion period, the shape index of DB2-9 and Xiacui in T1 was significantly lower than those in the other treatments; and during the three periods, the fruit shape index of Xiahui 8 in T2 was significantly lower than in the other treatments. During the expansion period, the L* value of DB2-9 and Xiacui in T3 and T4 was significantly lower than in T1; during the expansion and ripening periods, the L* value of Xiahui 8 in T2 was significantly higher than in T1. In the entire periods, the a* value of DB2-9 in T4 was significantly higher than in T1 and T2; at the ripening stage, the difference in the a* value of Xiahui 8 between treatments was not significant, and the a* value of Xiacui under T1 was significantly higher than under the other treatments. At the ripening stage, the C value of DB2-9 and Xiacui in T3 and T4 was significantly lower than in T1, while the differences among treatments were not significant in Xiahui 8. At the ripening stage, the a*/b* value of DB2-9 and Xiahui 8 under T3 and T4 was significantly higher than under T1 and T2, while the differences among treatments were not significant in Xiacui. During the ripening period, there was no significant difference in fruit firmness with skin and firmness without skin of DB2-9 among the treatments; during the expansion period, the firmness with skin and firmness without skin of Xiahui 8 in T4 was higher than in T1; during the three periods, the firmness with skin of Xiacui in T3 was significantly higher than in T1. The soluble solids content of Xiacui in T1 was higher than in the other treatments at the hard core and expansion stages, while the soluble solids content of DB2-9 and Xiahui 8 in T1 was significantly lower than in the other treatments at the expansion and ripening stages. The soluble sugar content of DB2-9 under T1 was significantly lower than under the other treatments during the expansion and ripening periods; the sucrose content, sorbitol content and total sugar content of Xiahui 8 under T2 were significantly lower than under T1 during the hard core stage, while they were significantly higher than under T1 during the ripening period; the soluble sugar content of Xiacui under T2 and T3 was lower than under T1 during the expansion period, while at the ripening stage, there was no significant difference in the glucose content, fructose content and total sugar content among the treatments in Xiacui. At the ripening stage, the quinic acid content and total acid content of DB2-9 under T1 were significantly lower than under the other treatments; at the hard core stage, the organic acid content of Xiahui 8 under T1 was significantly lower than under the other treatments, whereas the quinic acid content, malic acid content and total acid content of Xiahui 8 under T4 were significantly higher than under T1 at both the expansion and ripening stages; and at the ripening stage, the quinic acid content, malic acid content and total acid content of Xiacui in T3 and T4 were higher than in T1. In the expansion and ripening periods, the sugar-acid ratio of DB2-9 under T3 was significantly higher than under T1; in the ripening period, there was no significant difference in the sugar-acid ratio among the treatments in Xiahui 8; and the sugar-acid ratio of Xiacui under T2 and T3 was significantly lower than that under T1 and T4 in the three periods. [Conclusion] The application of 100 mg·L-1 GA3 significantly increased the mass of single fruit, SSC, total sugar content and sugar-acid ratio of DB2-9 at the ripening stage, while it had no significant effect on the pigmentation of the fruits; the exogenous application of 50 mg·L-1 GA3 increased the single fruit mass and SSC of Xiahui 8 at the three periods, as well as the total sugar content and sugar-acid ratio at the ripening stage, and significantly increased the L* value of the fruits at ripening; and the exogenous application of 50 mg·L-1 GA3 increased the mass of single fruit and firmness with skin of Xiacui in the three periods, as well as SSC and total sugar content in the ripening stage. Overall, the exogenous application of 100 mg·L-1 GA3 can improve the overall quality of fruits of DB2-9; the exogenous application of 50 mg·L-1 GA3 can improve the overall quality of fruits of Xiahui 8 and Xiacui.